PENDIDIKAN ILMU PENGETAHUAN SOSIAL BERBASIS C3 (COLLEGE, CARRIER, CIVIC LIFE) DAN LIFE SKILL UNTUK MEMBENTUK KARAKTER SISWA SEKOLAH MENENGAH PERTAMA - Anita Rinawati; Ary Purwantiningsih (Universitas Muria Kudus, 2021)
The purpose of this study is to analyze the application of C3-based Social StudiesEducation (College, Carrier, Civic Life) and Life Skills to form character in junior highschool students during the pandemic.The research method used is qualitative. The research subjects were students and socialstudies teachers of SMP Negeri 1 in Purworejo Regency. Data collection techniques usedwere observation and online interviews to prevent transmission. Data collection wascarried out in December 2020. Test the validity of the data using the triangulationtechnique. In the data analysis technique used data analysis includes 1) data reduction; 2) Data Presentation; and 3) Drawing conclusions.The results of the social studies education model by referring to the C3 framework andincorporating elements of Life Skills are very useful for the lives of students, including 1)Students will have a broad meaning of life skills, 2) Students are able to deal proactivelyand reactively in order to find solutions to problems, 3) The C3 Social Studies frameworkcan be a guide for students' readiness to enter higher education, career preparation andcommunity life as well as critical thinking skills, problem solving abilities, andcollaborative skills needed during the current pandemic.